The Role of AAA+ Proteins in Protein Repair and Degradation - James Shorter (Frontiers Research Topics, 2018)
ATPases Associated with diverse cellular Activities (AAA+) comprise a superfamily of proteins that are defined by the presence of the AAA+ domain containing canonical Walker A and B motifs required for ATP binding and hydrolysis. Members of this superfamily act on other proteins, DNA, RNA, or multicomponent complexes to affect their conformation or their assembly. There have been substantial advances in understanding the structure and mechanism of function of a large number of AAA+ proteins. In this Research Topic, review articles and original research papers discuss new aspects as well as provide a detailed overview of several AAA+ proteins, namely: ClpXP, Lon, ClpB, Hsp104, p97, AAA+ proteins of the proteasome, Rubisco activases, Torsin, Pontin, and Reptin.